Аналіз розподілу дефектів та неметалевих включень високоміцної TWIP-сталі Fe-25Mn-12Al-1,5C після електрошлакового переплаву - Ворон, М.М.; Семенко, А.Ю.; Тимошенко, А.М.; Шемет, В.Ж. (Physico-technological Institute of Metals and Alloys, 2024)
TWIP steels belong to the list of the most innovative materials of our time due to the combination of a high mechanical characteristics level and low density. The most high-strength alloys usually contain about 25-30 wt. % manganese and about 10 wt. % aluminum. Production of such steels is complicated by the peculiarities of their chemical composition. Due to the high content of manganese and aluminum, they are prone to components liquation by density, have a greater number of shrinkage defects and an increased number of sulfides, nitrides and oxides non-metallic impurities. This determines the use of effective refining methods, which include electroslag remelting (ESR). The paper shows a comparison of Fe-25Mn-12Al-1.5C alloy structure, type and amount of non-metallic inclusions after induction melting and after refining electroslag remelting. Electron microscopy of the samples and local chemical analysis of the phases showed a large number of non-metallic inclusions — sulfides, phosphides, and oxynitrides. After refining process, it was shown that electroslag remelting contributes to a noticeable decrease of nitrogen and sulfur content, and as the result — it lowers the number of related of non-metallic inclusions. However, it seems to be an insufficiently effective method of refining materials like TWIP-steels. Relatively large size of the non-metallic inclusions, low phosphides refining ability and the crystallization conditions under which a directionally crystallized structure forms, may be noticed among the disadvantages of the ESR method. It was also established that in crystallizer zones, close to the bottom and walls, metal refines worse than its central volumes. Upper part of the ingot has shrinkage and sub-shrinkage zones enriched with gas-shrinkage defects, so it can be called a problem zone. In general, it is shown that the ESR method is not capable to solve a problem of refining high-manganese TWIP steels with a high aluminum content to the required extent.